Reconstruction of Extensor Tendon Dislocation Due to Chronic Sagittal Band Rupture of the Thumb Metacarpophalangeal Joint: A Case Report. Issue 3 (July 2016) - Hibino, Naohito; Hamada, Yoshitaka; Sato, Ryosuke; Wada, Kazuma; Kondo, Kenji; Sairyo, Koichi
Abstract : Case: We report a case of recurrent dislocation of the extensor pollicis longus and extensor pollicis brevis tendons due to chronic rupture of the radial sagittal band of the metacarpophalangeal joint of the thumb. Conclusion: Successful restabilization of these tendons was achieved by transferring a half-slip of the abductor pollicis brevis tendon.